Vasculitis integrated clinical assessment database: a data management system to support studies into systemic vasculitis. - Wilson AS; Bacon PA; Young SP; Carruthers DM (JRC: Journal of Clinical Rheumatology, 2010)
BACKGROUND: The systemic vasculitides are characterized by immune inflammation affecting blood vessels, which can lead to organ and tissue damage. Treatment has improved but optimum long-term management still remains unsatisfactory, requiring ongoing therapeutic studies. These often base their measures of efficacy on the outcome of clinical assessments which include the Birmingham Vasculitis Activity Score and the Vasculitis Damage Index. OBJECTIVES: Efficient management of assessment data is complex and often hampered by working with time-consuming paper-based systems. The Vasculitis Integrated Clinical Assessment Database (VICAD) was created to improve the process. METHODS: VICAD was developed using Microsoft Access. Visual Basic for Applications and the Data Access Objects Application Programming Interface provide the functionality to assist with scoring, calculation of results, and storing of data. RESULTS: VICAD is an efficient system for managing data. Evaluation of its use showed an improvement in the completeness of patient assessments from 77% (paper based: n = 44) to 98% (computer based: n = 30). During development clinicians (n = 4) rated it at 8/10 for its layout and visual presentation and 8/10 for easy to use (intuitiveness and navigability). CONCLUSIONS: The development of an integrated and standardized system of data collection (VICAD) helps to support clinical decision making processes and report findings in a more timely manner. It is available free for use and modification under the GNU General Public License. The open source nature of VICAD could help to inform the design of other databases where management of complex information into important multisystem diseases is needed.